Intraoperative sentinel lymph node dyeing during laparoscopic ilio-obturatory lymphadenectomy in patients with prostate cancer - Sieczych, Artur; Paluchowska, Beata; Wiechno, Paweł; J. Marczyński, Piotr; Ruka, Włodzimierz (Contemporary Oncology/Współczesna Onkologia, 2001)
From 29.07.1998 to 20.12.2000 laparoscopic ilio-obturatory lymphadenctomy was performed in 67 patients with prostate adenocarcinoma, initially qualified to radical teleradiotherapy. In 17 initial patients authors attemped to identify intraoperatively a sentinel lymph node using Patentblau V dye. No successful identification was observed. Authors resigned from the attempt of sentinel lymph node identification in further patients.